THE ROLE AND STRATEGY OF FARMERS IN FACING AGRIBUSINESS RISKS - Muhamad Solekan (INJOSEDU: International Journal of Social and Education, 2025)
Farmers have a very important role in the agribusiness sector, especially in dealing with various risks that can affect agricultural output. They are not only responsible for producing food, but also act as resource managers, local economic actors, and guardians of environmental sustainability. Farmers must be able to adapt to changes that occur, be it climate change, market price fluctuations, or technological developments. To deal with agribusiness business risks, farmers can apply several effective strategies. This study discusses the roles and strategies of farmers in dealing with agribusiness business risks that are often influenced by various factors, such as climate change, market price fluctuations, pests and diseases, and uncertainty of government policies. Farmers have a crucial role as resource managers, decision makers, innovators, financial managers, and collaborators in their efforts to reduce the impact of various risks that can threaten the sustainability of agribusiness businesses. The strategies implemented include business diversification, technology adoption, wise financial management, strengthening networks and cooperation, and adaptation to environmental and market changes. The results of the study indicate that a combination of proactive roles and well-planned strategies can increase the resilience and success of farmers in dealing with agribusiness business risks. It is important for farmers to continue to develop skills, strengthen networks, and adopt appropriate technologies to reduce uncertainty and improve the sustainability of their agribusiness.